Quest for the queen - Abbott, Tony.; Merrell, David Webber, 1973- (New York : Scholastic, 2000)
Princess Keeah competes in the Quest to try to win the prize which might break the magic spell on her mother.
"A Little Apple paperback."
410
Accelerated Reader AR
Keywords: Magic -- Juvenile fiction; Droon (Imaginary place) -- Juvenile fiction; Fantasy fiction